1995
DOI: 10.1051/ject/1995273137
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Monitoring During Extracorporeal Membrane Oxygenation: The Role of Thrombelastography

Abstract: Patients undergoing extracorporeal membrane oxygenation (ECMO) are at an increased risk for developing coagulopathies due to the adverse effects of extracorporeal circulation on the hemostatic mechanism. Methods of determining causative factors of bleeding diathesis are often inconsistent and non-specific. ECMO patients require aggressive transfusion therapy with autogenic blood products to stabilize and maintain hemostasis. The present study evaluated the coagulation status of newborn patients undergoing ECMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…TEG and ROTEM provide information about anticoagulation, thrombosis, platelet function, and fibrinolysis and can assist in decision-making with respect to both heparin infusion rate and administration of blood products or coagulation factors. This assay is poorly studied in the ECMO population and rarely used with nearly 60% of ECMO programs reporting that they never obtain TEG in their patients (2,19). However, TEG and ROTEM may be useful adjuncts for managing anticoagulation in patients in ECMO and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…TEG and ROTEM provide information about anticoagulation, thrombosis, platelet function, and fibrinolysis and can assist in decision-making with respect to both heparin infusion rate and administration of blood products or coagulation factors. This assay is poorly studied in the ECMO population and rarely used with nearly 60% of ECMO programs reporting that they never obtain TEG in their patients (2,19). However, TEG and ROTEM may be useful adjuncts for managing anticoagulation in patients in ECMO and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the TEG flat line reading had no relation to the perioperative bleeding [ 210 ]. However, other studies showed that the conventional TEG parameters were effective to monitor anticoagulation [ 211 ] and to predict coagulopathy in adults on ECMO patients [ 212 ].…”
Section: Reviewmentioning
confidence: 99%
“…The 2 most common viscoelastic monitoring techniques are TEG and ROTEM. 58,59 These techniques are performed differently but result in similar information that has been most widely used in transfusion medicine.…”
Section: Teg Rotemmentioning
confidence: 99%
“…The main categories that are most discussed for viscoelastic monitoring are phase 1: time to initial fibrin/clot formation; phase 2: rate of clot formation; phase 3: maximal clot strength; and phase 4: lysis (Table 3). 59,60 Finally, another potential benefit of this monitoring strategy is the addition of enzymes that eliminate heparin (ie, heparinase). This allows the team to simultaneously monitor the effects of heparin on the viscoelastic laboratory test result and the patient's underlying coagulopathy.…”
Section: Teg Rotemmentioning
confidence: 99%
See 1 more Smart Citation